2019
DOI: 10.1016/j.vaccine.2018.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of adult vaccinations: A systematic review

Abstract: Background: Coverage levels for many recommended adult vaccinations are low. The cost-effectiveness research literature on adult vaccinations has not been synthesized in recent years, which may contribute to low awareness of the value of adult vaccinations and to their under-utilization. We assessed research literature since 1980 to summarize economic evidence for adult vaccinations included on the adult immunization schedule. Methods: We searched PubMed, EMBASE, EconLit, and Cochrane Library from 1980 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 121 publications
1
61
0
3
Order By: Relevance
“…Despite national recommendations 43,44 , vaccine coverage among adults in high-income countries is uneven 45 (vaccine coverage for herpes zoster, which causes shingles, among adults aged 60 or over in the United States was 24% compared with 65% for influenza among those aged 65 or over), and very low or not even available in most low-and middle-income countries 46 . Yet, several studies have shown good cost-effectiveness of adult vaccinations against influenza, pneumococcal infection, shingles, HPV and tetanus-diphtheria-pertussis 47 .…”
Section: Vaccination Is a Lifetime Investmentmentioning
confidence: 99%
“…Despite national recommendations 43,44 , vaccine coverage among adults in high-income countries is uneven 45 (vaccine coverage for herpes zoster, which causes shingles, among adults aged 60 or over in the United States was 24% compared with 65% for influenza among those aged 65 or over), and very low or not even available in most low-and middle-income countries 46 . Yet, several studies have shown good cost-effectiveness of adult vaccinations against influenza, pneumococcal infection, shingles, HPV and tetanus-diphtheria-pertussis 47 .…”
Section: Vaccination Is a Lifetime Investmentmentioning
confidence: 99%
“…Notably, the efficacy of vaccines against IAV infections can fluctuate and there is a significant immune response variability across the population. Factors such as previous exposure to IAV infections or vaccines, age, and the closeness of the match between the vaccine and circulating strains are important to explain differences in vaccine effectiveness between seasons and group populations [44,46,[150][151][152]. However, multiple reports have demonstrated that the host genetic background and polymorphisms on key immune response genes modulate the immune response to infection or vaccination [153][154][155][156][157][158][159][160].…”
Section: Snps In Genes That Influence the Iav Vaccine Responsementioning
confidence: 99%
“…For influenza, the implementation of immunisation campaigns throughout the world have resulted in decreases of both mortality and morbidity [7,8]. Although usually focused on younger populations for epidemiological and practical reasons, vaccination in most age groups, including adults, is considered highly cost-effective [9,10].…”
Section: Introductionmentioning
confidence: 99%